(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The spread of urological pathology among the population of the country makes it necessary to look for methods to improve the effectiveness of patient treatment, and the availability and choice of the most rational and acceptable treatment methods for a particular patient is an important condition for restoring public health. The main task facing the healthcare system of the Republic is to provide quality medical services and ensure accessibility for all segments of the population. This includes not only state but also private medical institutions, where the focus is on the quality training of medical specialists and the improvement of their qualifications, with an emphasis on the use of modern technologies.